Percepción sobre la brecha salarial de género en la ciudad de Tarija – Bolivia - Vásquez Fernández, Bernardino Jesús (2019)
The gender wage gap is defined as the difference between the average salary of men and that of women, where women earn less than men for doing the same work, usually caused by inequalities in work, education and family responsibilities that women have. The research seeks to determine if the wage gap presents significant differences in the city of Tarija, based on its main characteristics, causes, effects and alternatives to reduce it. The study applied a thousand opinion surveys, through a non-probabilistic sampling by sex and age quotas, in the city of Tarija in Bolivia, in the months of April and May of 2019. Some of the most important results indicate that the salary gap is 32% between men and women. The average income of men is Bs 3304 per month (approximately USD$454), while the average income of women is Bs 2495 per month. (Approximately USD$358). The main causes are seniority, professional training and work experience. Women devote more hours to domestic activities and family care than men. The main consequences are the limitation of women to make decisions, greater dependence on other people, low self-esteem, lower pensions and impoverishment. Among the measures to reduce the gap, are the promotion of women to managerial positions, clearer remuneration policies, promote an equitable work in domestic household chores.